Optimal incorporation of multiple distributed generation units based on a new system maximum loadability computation approach and vortex searching algorithm - Y. Latreche; H. R. E. H. Bouchekara; M. S. Javaid; M. M. Aman; H. Mokhlis; F. Kerrour (Institute of Advanced Engineering and Science, 2019)
In this paper, the optimal incorporation of distributed generation (OIDG) units for the maximization of the system‟s loadability is investigated (based on sizing and siting). To this end a new computational approach for computing maximum loadability of the system is developed. This approach has been compared with the classical one on different radial test systems (RTS) and is found to be faster and more accurate. The OIDG problem is formulated mathematically as an optimization problem with the objective function to maximize system‟s loadability, the imposed constraints are; voltage limits, thermal limits and DG penetration level. The optimization algorithm used is to solve the OIDG problem is the Vortex searching algorithm (VS). The tested radial distribution systems are the standard 33-bus and 69-bus systems. This paper also discusses some other interesting findings about VS algorithm.